Study on the interconnection failure in lead-free soldered assemblies - Xu, Luhua (2008)
Lead-free solders have replaced tin-lead solders in electronic products due to European Union laws on restriction of hazardous substances such as lead (Pb) since July 1st, 2006. The electronic industry is prepared for lead-free solder reflow manufacturing of electronics assemblies. Solder is the weakest link material in electronic assemblies and it often causes solder joint failures. Hence, lead-free solder joint failure mechanism subject to thermal, mechanical and electrical loadings is studied in this thesis. Solid state IMC growth behavior between 95.5Sn-3.8Ag-0.7Cu solder and Cu-pad or Ni-barrier layer subject to isothermal and thermal cycling (TC) aging was investigated. An integrated IMC growth model as a function of temperature and time for TC aging is proposed. IMC interface failure subject to TC aging was characterized. Mechanical properties of IMC layers and strain-rate dependant properties of solder alloy were characterized by nano-indentation. Electromigration effect on IMC growth behavior and failure at the cathode and anode solder joint interfaces were analyzed. Electromigration-induced back stress and stress gradient were analyzed by studying the movement of nano-indentation marker subject to electrical current induced stressing. The effect of thermal aging on Kirkendall void formation and its subsequent failure mechanism subject to board level impact drop reliability test was investigated.